The Role of Risk Management in Strengthening the Impact of Financial Literacy on Investment Decisions - Lambe, Kristian Hoegh Pride; Patiung, Naomi; Latiep, Ifah Finatry (Accounting Profession Journal (APAJI), 2025)
This study aims to analyze the role of risk management as a moderating variable in strengthening the relationship between financial literacy and investment decisions. Using a quantitative approach, data were collected from 50 respondents in Indonesia who had at least one year of investment experience. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results showed that financial literacy has a positive but insignificant effect on investment decisions. In contrast, risk management is proven to have a positive and significant effect on investment decisions, and is able to significantly moderate the relationship between financial literacy and investment decisions. These findings confirm that financial literacy alone is not enough; risk management skills are essential to improve the quality of investment decision making. This study provides theoretical contributions by integrating financial literacy and risk management as important factors in investment behavior, and offers practical recommendations to improve risk literacy and awareness in the community.